Will the white blood cells tell? A potential novel tool to assess broiler chicken welfare - Ribeiro, Laura Raquel Rios; Sans, Elaine Cristina de Oliveira; Santos, Ricardo Martins; Taconelli, Cesar Augusto; de Farias, Roberta; Molento, Carla Forte Maiolino (Frontiers in Veterinary Science, 2024)
This study assessed qualitative and quantitative leukocyte evaluation as potential broiler chicken welfare indicators, contributing to the limited literature on white blood cell (WBC) morphology as a diagnostic tool for welfare. Broiler chicken welfare within four poultry houses (PH) 1 to 4, each on a different farm, was assessed using on-field indicators of affective states and health, and WBC and morphology were performed. Affective states were evaluated using the Qualitative Behavior Assessment (QBA) and 25 behavioral expressions were scored on visual analogue scales (VAS) and grouped in two groups. Lameness, footpad dermatitis, dermatitis on the breast and abdominal areas, hock burn, and feather cleaning were assessed as health indicators. Blood samples were collected and differential leukocyte counts were performed, and a cell score was created for recognition, classification and interpretation of morphologic diversity of heterophils and lymphocytes. In addition, the heterophil to lymphocyte ratio (H/L) was determined. Descriptive statistics and generalized linear models for binomial responses were used to analyze the results. The PH4 differed from the other farms, showing a higher frequency of birds within QBA group 1 (‘Attentive’ to ‘Desperate’), while birds in PH1, 2 and 3 were more frequently in QBA group 2 (‘Relaxed’ to ‘Positively occupied’). Elevated proportions of heterophils in birds from PH4 (0.61, CI95%: 0.58; 0.64) and PH3 (0.60, CI95%:0.57; 0.63) suggested higher stress levels and inflammatory response. The birds in PH2 and 4 exhibited higher frequencies of health issues, such as dermatitis and lameness and also higher proportions of abnormalities in WBC number and morphology. The PH3 and 4 exhibited higher H/L of 3.03 and 2.58 respectively, consistent with the on-field health and behavioral indicators. Blood samples from birds in PH2 and PH4 showed a proportion of 90% of toxic change heterophils, while in PH1 and PH3 it was 70%, i.e., birds from all PH presented high levels of abnormal WBC morphology. The findings emphasize the multifactorial nature of welfare impairments, including environmental conditions, health, and affective states, highlighting the need for indicators that may reflect multiple welfare impacts, which can become powerful storytellers in the complex task of assessing animal welfare.